Pengaruh Profitabilitas, Likuiditas, Kepemilikan Institusional dan Kepemilikan Asing Terhadap Struktur Modal pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019 - Hasna Aini Sabrina; Risal Rinofah; Ratih Kusumawardhani (J-MAS (Jurnal Manajemen dan Sains), 2021)
This study aims to examine the effect of profitability, liquidity, institutional ownership and foreign ownership on the capital structure of mining companies listed on the Indonesia Stock Exchange. The period used in this study was 5 years (2015-2019). The nature of the research used in this study is descriptive and associative research with a quantitative approach. For the sampling technique, this study uses purposive sampling method, namely by selecting samples that meet predetermined criteria. Based on the existing criteria, 50 companies became the research sample. The data analysis technique used is multiple linear regression. Based on the results of the analysis, the profitability variable has a negative and significant effect on capital structure with a regression coefficient of -0.724 and a significance value of 0.024. The liquidity variable has a significant and significant effect on the capital structure with a regression coefficient of -0.151. and a significance value of 0.000. Institutional ownership has no and no significant effect on the company's capital structure with a regression coefficient of 0.708 and a significance value of 0.073. Meanwhile, foreign ownership has no and no significant effect on the capital structure of mining companies and is indicated by a regression coefficient of -0.006 and a significant value of 0.957 is obtained.